Ellagic acid attenuates post-cerebral ischemia and reperfusion behavioral deficits by decreasing brain tissue inflammation in rats - Khadijeh Hassonizadeh Falahieh; Alireza Sarkaki; Mohammadamin Edalatmanesh; Mohammad Kazem Gharib Naseri; Yaghoob Farbood (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): Cerebral ischemia/reperfusion (I/R) causes brain inflammation that ultimately causes long time brain function disturbances. We aimed to evaluate the effect of ellagic acid (EA) on anxiety, depression, locomotion behaviors, blood-brain barrier (BBB) permeability, brain edema, and inflammation in male rats with cerebral I/R. Materials and Methods: Sixty male Wistar rats (250-300 g) divided into 6 groups randomly with 10 in each: 1) Sham+Veh; rats submitted to the surgery without any I/R and received vehicle (10% DMSO in normal saline 5 ml/kg, gavages). 2) I/R+Veh; 3-5) I/R+EA; I/R rats received 50, 75 and 100 EA mg/kg, by gavages 3 times daily for one week. The cerebral I/R injury was induced by clamping the bilateral common carotid arteries for 20 minutes followed by reperfusion. Behaviors were tested one week after treatment, and brain tissue cytokines were measured by special ELISA kits. Results: Cerebral I/R disrupted BBB function (P<0.001), increased brain water content (P<0.01), anxiety-like (P<0.001), depression-like (P<0.001) behaviors and cytokines in the brain tissue (P<0.001), while decreased locomotion and exploratory behaviors significantly (PConclusion: The results suggest that EA could be a potential therapeutic agent against cerebral I/R, possibly through its intertwined anti-inflammatory effects. Further research is required to investigate the involved mechanisms in details.